Locals’ Claims of Rights and Access to Forest Resources in Three Forest Management Regimes in Gunungkidul Regency, Yogyakarta - Madjid, Muhammad Iqbal Nur Madjid; Dwiko, Dwiko Budi Permadi; Wahyu, Wahyu Wardhana; Ratih , Ratih Madya Septiana (Jurnal Wasian, 2022)
One of state forest areas managed by three management regimes is Bunder forest area, Gunungkidul, Yogyakarta. Three management regimes are the production forest of KPH Yogyakarta, the conservation forest of Tahura, and the educational forest of KHDTK Wanagama I. The differences of management regimes are thought to affect the actual interaction pattern of villagers with the forest. This research aims to compare the actual rights and access of villagers to Bunder forest area in three management regimes in the hope of finding more effective forest management patterns. This research used a qualitative approach through the case study method of the interaction villagers of Bunder, Banaran, Ngleri, and Gading villages with the surrounding forests. The results show that forest management regimes affects the way villagers can access the forests. The aggregate value of the actual rights received by the villagers to the production forest of KPH Yogyakarta is higher than the educational forest of KHDTK Wanagama I. The lowest is management regimes in conservation forest of Tahura. Based on the access mechanisms that empower villagers, the educational forest regime of KHDTK Wanagama I is higher than the production forest regime of KPH Yogyakarta and the conservation forest regime of Tahura. This research recommends defining rights and access to increase certainty about the benefits of forest resources.